Answer:
<h2>
![( f - g)(x) = \frac{2x - \sqrt{x} + 14 }{3x}](https://tex.z-dn.net/?f=%28%20f%20-%20g%29%28x%29%20%20%3D%20%20%5Cfrac%7B2x%20-%20%20%5Csqrt%7Bx%7D%20%2B%2014%20%7D%7B3x%7D)
</h2>
Step-by-step explanation:
![f(x) = \frac{2x + 6}{3x} \\ \\ g(x) = \frac{ \sqrt{x} - 8}{3x}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B2x%20%2B%206%7D%7B3x%7D%20%20%5C%5C%20%20%5C%5C%20g%28x%29%20%3D%20%20%5Cfrac%7B%20%5Csqrt%7Bx%7D%20%20-%208%7D%7B3x%7D%20)
To find ( f - g)(x) , subtract g(x) from f(x)
That's
![( f - g)(x) = \frac{2x + 6}{3x} - \frac{ \sqrt{x} - 8}{3x}](https://tex.z-dn.net/?f=%28%20f%20-%20g%29%28x%29%20%3D%20%20%5Cfrac%7B2x%20%2B%206%7D%7B3x%7D%20%20-%20%20%5Cfrac%7B%20%5Csqrt%7Bx%7D%20%20-%208%7D%7B3x%7D%20)
Since they have a common denominator that's 3x we can subtract them directly
That's
![\frac{2x + 6}{3x} - \frac{ \sqrt{x} - 8}{3x} = \frac{2x + 6 - ( \sqrt{x} - 8) }{3x} \\ = \frac{2x + 6 - \sqrt{x} + 8 }{3x} \\ = \frac{2x - \sqrt{x} + 6 + 8 }{3x}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%20%20%2B%20%206%7D%7B3x%7D%20%20-%20%20%5Cfrac%7B%20%5Csqrt%7Bx%7D%20%20-%208%7D%7B3x%7D%20%20%20%20%3D%20%20%5Cfrac%7B2x%20%20%2B%206%20-%20%28%20%5Csqrt%7Bx%7D%20-%208%29%20%7D%7B3x%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B2x%20%2B%206%20-%20%20%5Csqrt%7Bx%7D%20%2B%208%20%7D%7B3x%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B2x%20-%20%20%5Csqrt%7Bx%7D%20%2B%206%20%2B%208%20%7D%7B3x%7D%20)
We have the final answer as
<h3>
![( f - g)(x) = \frac{2x - \sqrt{x} + 14 }{3x}](https://tex.z-dn.net/?f=%28%20f%20-%20g%29%28x%29%20%20%3D%20%20%5Cfrac%7B2x%20-%20%20%5Csqrt%7Bx%7D%20%2B%2014%20%7D%7B3x%7D%20)
</h3>
Hope this helps you
When you have a power to a fraction, you simply take it by the top and then by the bottm.
So, split it into two: (2)^4 and (5)^4
Solve: (2)^4=16
(5)^4=625
So the fraction is: 16/625
Check to see if it reduces: It doesn't. (Odd and even numbers that have no common multiples).
Therefore, that's the answer.
Answer:
k = -2
Step-by-step explanation:
1. Substitute the point (2,-1) into the given equation 5x+ky=12. The first number is 2, the x-value. The second number is -1, the y-value.
5x + ky = 12
5(2) + k(-1) = 12
2. Simplify
5(2) + k(-1) = 12
10 + (-k) = 12
10 - k = 12
2. Isolate k
10 - k = 12
-k = 12-10
-k = 2 <= here multiply both sides by (-1)
k = -2
It will take 16 weeks to collect 400 cans
So 16 multipled by 25 would give you 400
I hope this helps sorry if not